Kinetic analysis and mechanistic aspects of autoxidation of catechins - Mochizuki, Manabu; Yamazaki, Shin-ichi; Kano, Kenji; Ikeda, Tokuji (Biochimica et biophysica acta, 2002)
A peroxidase-based bioelectrochemical sensor of hydrogen peroxide (H 2O 2) and a Clark-type oxygen electrode were applied to continuous monitoring and kinetic analysis of the autoxidation of catechins. Four major catechins in green tea, (−)-epicatechin, (−)-epicatechin gallate, (−)-epigallocatechin, and (−)-epigallocatechin gallate, were used as model compounds. It was found that dioxygen (O 2) is quantitatively reduced to H 2O 2. The initial rate of autoxidation is suppressed by superoxide dismutase and H +, but is independent of buffer capacity. Based on these results, a mechanism of autoxidation is proposed; the initial step is the one-electron oxidation of the B ring of catechins by O 2 to generate a superoxide anion (O − 2) and a semiquinone radical, as supported in part by electron spin resonance measurements. O − 2 works as a stronger one-electron oxidant than O 2 against catechins and is reduced to H 2O 2. The semiquinone radical is more susceptible to oxidation with O 2 than fully reduced catechins. The autoxidation rate increases with pH. This behavior can be interpreted in terms of the increase in the stability of O − 2 and the semiquinone radical with increasing pH, rather than the acid dissociation of phenolic groups. Cupric ion enhances autoxidation; most probably it functions as a catalyst of the initial oxidation step of catechins. The product cuprous ion can trigger a Fenton reaction to generate hydroxyl radical. On the other hand, borate ion suppresses autoxidation drastically, due to the strong complex formation with catechins. The biological significance of autoxidation and its effectors are also discussed.